Calcium use during paediatric in-hospital cardiac arrest is associated with worse outcomes. (April 2023) - Cashen, Katherine; Sutton, Robert M.; Reeder, Ron W.; Ahmed, Tageldin; Bell, Michael J.; Berg, Robert A.; Burns, Candice; Carcillo, Joseph A.; Carpenter, Todd C.; Michael Dean, J.; Wesley Diddle, J.; Federman, Myke; et al.
Abstract: Aim: To evaluate associations between calcium administration and outcomes among children with in-hospital cardiac arrest and among specific subgroups in which calcium use is hypothesized to provide clinical benefit. Methods: This is a secondary analysis of observational data collected prospectively as part of the ICU-RESUScitation project. Children 37 weeks post-conceptual age to 18 years who received chest compressions in one of 18 intensive care units from October 2016–March 2021 were eligible. Data included child and event characteristics, pre-arrest laboratory values, pre- and intra-arrest haemodynamics, and outcomes. Outcomes included sustained return of spontaneous circulation (ROSC), survival to hospital discharge, and survival to hospital discharge with favourable neurologic outcome. A propensity score weighted cohort was used to evaluate associations between calcium use and outcomes. Subgroups included neonates, and children with hyperkalaemia, sepsis, renal insufficiency, cardiac surgery with cardiopulmonary bypass, and calcium-avid cardiac diagnoses. Results: Of 1, 100 in-hospital cardiac arrests, median age was 0.63 years (IQR 0.19, 3.81); 450 (41%) received calcium. Among the weighted cohort, calcium use was not associated with sustained ROSC (aOR, 0.87; CI95 0.61–1.24; p = 0.445), but was associated with lower rates of both survival to hospital discharge (aOR, 0.68; CI95 0.52–0.89; p = 0.005) and survival with favourable neurologic outcome at hospital discharge (aOR, 0.75; CI95 0.57–0.98; p = 0.038). Among subgroups, calcium use was associated with lower rates of survival to hospital discharge in children with sepsis and renal insufficiency. Conclusions: Calcium use was common during paediatric in-hospital cardiac arrest and associated with worse outcomes at hospital discharge.